(untitled) (Research, Society and Development, 2022)
The present study aimed to estimate the temporal trend of confirmed cases of tuberculosis in northeastern Brazilian states from 2001 to 2020. This is an ecological time series study using public databases. Data were collected from the Notifiable Diseases Information System (SINAN/DATASUS). The information was arranged through descriptive statistics: mean, standard deviation, minimum and maximum. The tuberculosis incidence rate (TIR) was calculated according to sex and state and used for trend estimation, performed using JoinPoint regression. Correlation estimation was performed using the TIR with GINI coefficients, per capita income and sanitary sewage. The Northeast presented an average TIT of 46.15 cases (SD= 5.54) for every 100 thousand inhabitants. The highest TIRs were observed in Pernambuco with 60.15 cases/100 thousand inhabitants (SD=2.92), followed by Ceará with 50.69 cases/100 thousand inhabitants. (SD=5.02). The temporal trend of the Northeast, Rio Grande do Norte, Pernambuco and Sergipe was stationary (p>0.05). Maranhão presented a decrease of -6.7% in the general group between 2005-2012 and a general reduction of -2% in the entire time series. Ceará, Paraíba and Alagoas presented a decrease of -2.8%, -2.4% and -8.2% in the group of women, respectively. The state of Bahia showed a decrease in all groups, -11.2% (male), -4.1% (female) and -3.3% (general). Correlation results were not statistically significant (p>0.05). The Northeast, Rio Grande do Norte, Pernambuco and Sergipe showed a stationary trend, while Ceará, Paraíba, Alagoas and Bahia showed a decrease.